Development of wireless photoplethysmograph based health monitoring system - Nur Izzati Zainal (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
The demand for use in medical application of enhancing technology is gradually on the rise every year. All crucial devices currently used in hospitals for health-monitoring services, are wired. The use of wired equipment for applications of electrocardiogram (ECG) machine or photoplethysmography (PPG) may be cumbersome due to physical movement in ambulatory vehicles. The PPG embedded with wireless features make the best non-invasive alternative by being simple and low cost device. This thesis thus presents the development of wireless PPG based health monitoring system. The main objectives of this research are focusing on both establishing the hardware and software for a comprehensive overall system. The further analysis will be done based on full hardware and software architecture for developing and designing a complete device for wireless PPG based health monitoring system. The proposed methodology is based on the hardware block diagram, component selection, calibration and system integration. The integration of electronic components of microcontroller, PPG sensor, Bluetooth module and display module will make a complete prototype of the proposed system. A Graphical User Interface (GUI) is developed in Matlab software to capture and record the transmitted PPG signal from the PPG sensor. In this research, two prototypes are constructed for health monitoring system. The second prototype is the enhancement version of the first prototype in term of wiring, display and design. The results show that both prototypes developed for wireless transmission are performing appropriately. The range for of the proposed system with Bluetooth module can go up to sixteen meters for successful transmission of PPG signal. As a proof of concept, Heart Beat Count is measured from six subjects in sitting and standing positions. The PPG signals collected are also being analyzed in time domain and frequency domain using Kubios HRV software. The outcome shows that PPG signals is more stable when the person is in rest condition. With the positive results that has been obtained from this research, wireless PPG based health monitoring system is bound to be with convincing potential for future medical technology development.